Convergence Behaviour of Growth Triangle: The Case of IMT-GT - Dayang Affizzah, Awang Marikan; Ramli, N.; Mee-Sing, T (OMICS International, 2016)
Regional disparities and their evolution displayed a vital economic as well as political issue for most regions or countries (Blizkovsky, 2012). Due to realizing this shocking fact, it has drawn a lot of attention from all over the world to tackle this issue in order to avoid its adverse implication towards holistic economic development. The beauty of Indonesia-Malaysia-Thailand Growth Triangle (IMT-GT) is that it aims to increase the trade and investment among the three regions as it pursues private sector-led economic growth. However, evidence shows that the progress of development in this sub-region is either stagnant or slow. Hence, the aim of this study is to investigate the convergence hypothesis of the participating states and determine the reason behind each of the convergence behaviour portrayed. Non-linear time varying factor model namely Phillip and Sul has been employed in this study. The result implies that Negeri Sembilan is the only diverging group while the rest is converging. This phenomenon indicates that most of the states and provinces in this sub-region have positive performance towards the economic growth. Effective development planning can be done by policy makers after determining the performance of each of the states and provinces.